Perlindungan Hukum terhadap Konsumen Kosmetik Vegan Menurut Undang-Undang Jaminan Produk Halal Dikaitkan dengan Undang-Undang Perlindungan Konsumen: Studi Kasus Produk Sabun Strawberry Shower Gel The Body Shop - Annisa Ramadhani Utami; Anne Gunawati; Sariyah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The circulation of vegan cosmetic products in Indonesia has grown rapidly alongside increasing public awareness of natural, environmentally friendly, and cruelty-free products. However, vegan formulations do not necessarily fulfill the requirements of halal product assurance as regulated under Law Number 33 of 2014 concerning Halal Product Assurance. The focus of this study is to examine the legal protection of consumers regarding the distribution of Strawberry Shower Gel products by PT Monica Hijau Lestari under the Consumer Protection Law in relation to the Halal Product Assurance Law, as well as the responsibility of PT Monica Hijau Lestari for the circulation of such vegan cosmetic products. This research applies the theories of legal certainty and legal liability as the analytical framework. The research method used is normative-empirical juridical research with statutory, conceptual, and field study approaches. Primary data were obtained through interviews with Dr. K.H.A. Bazari Syam, M.Pd.I, Chairman of the Indonesian Ulema Council (MUI) of Banten Province, and Nurul Khairani, Manager of Research and Education at YLKI, as well as interviews with consumers using Strawberry Shower Gel products. Secondary data were collected through literature studies of laws and regulations, books, journals, and related documents. The results of the study indicate that Strawberry Shower Gel products have obtained BPOM distribution permits, thereby fulfilling aspects of safety, quality, and market eligibility. However, the products have not fully met the assurance of halal certainty because vegan formulations cannot be used as the sole basis for determining the halal status of a product. The vegan concept only emphasizes the absence of animal-derived ingredients, whereas halal encompasses the assessment of ingredients, production processes, facilities, production equipment, and the halal assurance system as a whole. The use of vegan formulations in products also has the potential to create confusion among the public, particularly Muslim consumers, who may assume that vegan products are automatically halal. Based on the findings, increased transparency of product information and the acceleration of halal certification for cosmetic and bath and body products are necessary to provide legal certainty, consumer protection, and a sense of security for Muslim consumers in using vegan cosmetic products in Indonesia.